Serum Level of Rheumatoid Factor and Anti-Nuclear Anti bodies in Patients with Helicobacter Pylori Related Gastric Lesions - Abd el-Khallek, Enjy Yousry; Zaki, Sami mohamed; Abo el-Ela, Abeer Mohammed; Allam, Mohammed Abd el-Rashid; Ismail, Mahmoud Bastawy; Abd el-Rashid, Mahmoud (Journal of medical and pharmaceutical sciences, 2018)
The exact etiology of systemic rheumatic diseases is unclear, but it has long been suggested that exposure to certain environmental agents, such as bacterial infection, in genetically predisposed individuals may be the trigger for the initiation of autoimmune processes. Helicobacter pylori (H. pylori) is one of the most widely studied infectious agents proposed as agents triggering autoimmune response. Eighty dyspeptic patients were selected in our prospective case-control study, for evaluating the serum level of rheumatoid factor (RF) and anti-nuclear antibody (ANA) in patients with H. Pylori related gastric lesions. According to endoscopic findings and Rapid Urease Test (RUT), our patients were divided into 4 groups; 20 patients with positive endoscopic findings and positive RUT (I-a), 20 patients with positive endoscopic findings and negative RUT (I-b), 20 patients with negative endoscopic findings and positive RUT (II-a) and 20 patients with negative endoscopic findings and negative RUT (II-b). For all patients group, full clinical evaluation, routine laboratory investigations, upper endoscopy with RUT, serum level of RF and ANA were done. Serum levels of RF and ANA among the total H. pylori-infected subjects, were significantly higher in comparison to uninfected groups, furthermore, serum levels of RF and ANA were higher in H. pylori infected patients with gastric lesions as, peptic ulcer, gastritis andduodenitis. Further study for evaluating the effect of H. pylori eradication on serum levels of RF and ANA is highly recommended.